THE EFFECT OF THE USE OF GALLERY WALK LEARNING METHODS ON STUDENT LEARNING OUTCOMES IN SMP NEGERI 1 ENDE - Reni Maria Jimun; Ilyas Ilyas; Adrianus Nasar (ScienceEdu: Jurnal Pendidikan IPA, 2020)
This study aims to determine the effect of the use of the gallery walk method of learning outcomes of VII grade students of SMP Negeri 1 Ende in the 2019/2020 Academic Year. This type of research is survey research with an ex-post facto research design. The population in this study were students of class VII A, B, C of SMP Negeri 1 Ende, with a sample of 51 students who were obtained using a simple random sampling technique. Data obtained through interviews and documentation, in the form of student learning outcomes data. Data analysis was used by t-test. The results showed that learning activities using the gallery learning method go students learning outcomes, which obtained the value of t =14.531, with =12.510. the value of sig. (2-tailed) 0,000 < 0,05 with α = 0,05.